Development of multiplex RT‐PCR assay for simultaneous detection of four viruses infecting apple (Malus domestica). (30th January 2022) - Nabi, S.U.; Madhu, G.S.; Rao, G.P.; Baranwal, V.K.
Abstract: The major viruses infecting apple cultivars throughout the world including India are apple mosaic virus (ApMV), apple stem pitting virus (ASPV), apple stem grooving virus (ASGV), apple chlorotic leaf spot virus (ACLSV), and recently, a new virus, apple necrotic mosaic virus (ApNMV), was reported from mosaic‐infected apple cultivars in India. The aim of this study was to detect the ApNMV virus along with the other three viruses (ApMV, ASPV and ASGV) simultaneously by multiplex RT‐PCR. Four primer‐pair‐produced amplicons of 670, 550, 350 and 210 bp corresponding to ApNMV, ApMV, ASPV and ASGV, respectively, were found to be specific for these viruses when tested individually. The annealing temperature (55°C), primer concentration (0·8 µ l) and other components of the master mix were standardized for the development of one‐step m‐RT‐PCR assay. The m‐RT‐PCR protocol developed was further validated with 30 samples from seven symptomatic or asymptomatic apple cultivars, which revealed the presence of more than one virus in these cultivars. Most of the viruses were found to be present either alone or in mixed infection; however, ASPV was more common in tested cultivars. An easy, cost‐effective and rapid multiplex RT‐RCR protocol was developed to detect the four viruses, which infect apple plants either in individually or together in the field. This assay will help in the surveying and indexing of apple germplasm and the distribution of all four viruses in the apple growing regions of India. Abstract : Significance and Impact of the Study: In India, a new virus, apple necrotic mosaic virus (ApNMV), has been found to infect the apple trees along with ApMV, apple stem pitting virus (ASPV) and apple stem grooving virus (ASGV). This study was designed to detect the ApNMV along with three other viruses (ApMV, ASPV and ASGV) simultaneously using multiplex RT‐PCR in a single tube. The assay developed in this study will be an effective detection tool for large‐scale surveys and indexing of large apple germplasm for the production of virus‐free planting material in temperate fruits. This will also help in studying the distribution of all the four viruses in apple growing regions of India and abroad.